An Overview of Remote Sensing for Mountain Vegetation and Snow Cover - Xiaohua Hao; Hongyi Li; Xufeng Wang; Xiaoyan Wang; Xiaodong Huang; Jian Bi (Remote Sensing, 2022)
Climate change has profoundly impacted elements of land surface at high latitudes and elevations, especially snow and vegetation [...]